The Role of Innate and Adaptive Immunity in Staphylococcal Scalded Skin Syndrome: A Systematic Literature Review - Isramilda; Andi Ipaljri (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: The innate immune system provides immediate protection in the event of an infection, while the adapted immune system provides a more specific response and has the ability to remember specific pathogens, thereby protecting the body from similar infections in the future. This study aimed to present the role of innate and adaptive immunity in staphylococcal scalded skin syndrome (SSSS). Methods: The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the role of innate and adaptive immunity in staphylococcal scalded skin syndrome. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Results: Five studies were included in this study. A combination of innate and adapted immune systems work together to overcome SSSS infections. Conclusion: The innate immune system provides a rapid initial defense, while the ad apted immune system provides a more specific response and the ability to form immune memory.